Analysis of The Economic Structure in the north of Lao PDR - CHANTHAVONE, Thongphanh; XIONGTOUA, Tongvang; SENGDALA, Chansamone; KEODOUANGKHAM, Phavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
This paper aims to analyze of the economic structure in the north of Lao PDR. The results of the study show that the industry investment had the most value among agricultural and service sectors in northern parts of Laos. Its number was 21,779,985 million kip covering 69.56% of total investment. Service investment ranged the second with value of 7,113,265 million kip or 22.72% and agriculture investment covered only 7.73%. Income and GDP of northern provinces of Laos was on the rising trend since 2011-2013, but it dropped in 2014 and then recovered again in 2015. For the 3 sectors of economic structure, agriculture had the most value covering 48.10% of total income and GDP. Service sector ranged the second as it covered 30.70% and industry investment was the least value with only 21.20% of the GDP proportion. The dynamic OLS estimator of the investment links to economic growth in long term of 8-northern provinces. Agriculture investment has positive link to economic growth with the significance of 0.01. It means that the more investment on Agriculture, the more GDP growth rate in a long term. Investment on industry has negative link to the regional economic growth with the significance of 0.01. It means that the cost of industrial investment would be high in the beginning and become lower in the long future. And investment on service has positive link on regional economic growth with significance of 0.01. It means the more investment on this field, the more economic growth in the long term. For testing granger causality between 3 investment sectors and economy of 8 Northern provinces of Laos showed that: The testing granger causality GDP on agricultural investment, the GDP had no granger causes on agricultural investment in a short term. However, agricultural investment had granger causes on economic growth, the industry investment and economic (GDP) of 8 Northern provinces of Laos. The short terms, Economic (GDP) on industry investment is accepted null hypothesis, it means the GDP is not granger causes on industry investment but the industry investment on GDP is rejected null hypothesis. That means the industry investment is granger causes GDP, and economy (GDP) on service investment is rejected null hypothesis. It means the GDP is granger causes service investment, but the service investment on GDP is accepted null hypothesis which is not granger causes GDP. The long terms economic (GDP) on three investment sectors and the 3 investment sectors on Economic (GDP) are also rejected null hypothesis that means all of those affect each other